2009
DOI: 10.1080/01635580903285148
|View full text |Cite
|
Sign up to set email alerts
|

Black Raspberry Components Inhibit Proliferation, Induce Apoptosis, and Modulate Gene Expression in Rat Esophageal Epithelial Cells

Abstract: We have shown that a diet containing freeze-dried black raspberries (BRB) inhibits the development of chemically-induced cancer in the rat esophagus. To provide insights into possible mechanisms by which BRB inhibit esophageal carcinogenesis, we evaluated an ethanol (EtOH) extract of BRB, and two component anthocyanins (cyanidin-3-O-glucoside and cyanidin-3-O-rutinoside) in BRB, for their effects on growth, apoptosis and gene expression in rat esophageal epithelial cell lines. The EtOH extract and both anthocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 42 publications
2
39
0
2
Order By: Relevance
“…Again, the alcohol extract was found to be the most effective in down-regulating AP-1 and NF-κB activities, and its effects were mediated via inhibition of mitogen-activated protein kinase (MAPK) activation and inhibitory subunit κB phosphorylation, respectively. Subsequent studies utilizing cultured human oral and colon cancer cells, and rat esophageal epithelial cells of differing tumorigenic potential, confirmed that an alcohol extract of BRB was the most effective of several extracts tested in inhibiting cell proliferation and in stimulating apoptosis and cell differentiation (26)(27)(28).…”
Section: Studies To Identify the Anthocyanins As Active Inhibitory Comentioning
confidence: 70%
“…Again, the alcohol extract was found to be the most effective in down-regulating AP-1 and NF-κB activities, and its effects were mediated via inhibition of mitogen-activated protein kinase (MAPK) activation and inhibitory subunit κB phosphorylation, respectively. Subsequent studies utilizing cultured human oral and colon cancer cells, and rat esophageal epithelial cells of differing tumorigenic potential, confirmed that an alcohol extract of BRB was the most effective of several extracts tested in inhibiting cell proliferation and in stimulating apoptosis and cell differentiation (26)(27)(28).…”
Section: Studies To Identify the Anthocyanins As Active Inhibitory Comentioning
confidence: 70%
“…Our laboratory reported that an ethanol extract from black raspberries selectively inhibited the growth and induced apoptosis in a highly tumorigenic rat esophageal epithelial cell line (RE-149 DHD) but not in a weakly tumorigenic line (RE-149). The uptake of the anthocyanins from the extract into RE-149 DHD cells far exceeded their uptake into RE-149 cells, which may have accounted for the selective effects of the extract on growth and apoptosis of RE-149 DHD cells (Zikri et al 2009). The concentrations of anthocyanins/anthocyanidins or extract fractions required to elicit anti-carcinogenic effects in vitro are much higher (∼10-200 μM) than the levels of these compounds observed in the blood of animals administered anthocyanin-containing diets or juices (∼2-25 nM).…”
Section: In Vitro Studiesmentioning
confidence: 98%
“…The plant antioxidant, anthocyanin, a component in LPva extract (Norhaiza et al, 2009), was recently shown to induce apoptosis in human hepatoma cells (Shin et al, 2009) and in rat esophagal epithelial cells (Zikri et al, 2009). Apoptosis-initiated exfoliation of superficial bladder cells is an important defense mechanism during UTI (Klumpp et al, 2006).…”
Section: Lpva Induces Apoptosis In Bladder Epithelial Cellsmentioning
confidence: 98%
“…Additionally, the increasing number of infections caused by antibiotic resistant UPEC (Gupta et al, 1999) suggests the need for alternative treatment options. Interestingly, anthocyanins, antioxidant components of fruits and plants, have been shown to be apoptosisinducing (Shin et al, 2009;Zikri et al, 2009). These components have recently been identified in the extract of Labisia pumila var.…”
Section: Introductionmentioning
confidence: 97%